Manejo fisioterapéutico de la artrosis cervical en los pacientes antendidos en el hospital del IESS durante el periodo julio- diciembre del 2009 - Arias Vallejo, Mónica Isabel (2010)
The present investigation begin of the selection of an important topic based on the idea of contributing knowledge about the treatment and recovery of lesions that frequently they affect the physically active population and the elderly, being the case of the cervical artrosis. This consists of a content chart that summarizes the order in that the content of the investigation will be developed; next it offers a global vision of the topic to investigate and once identified the problem, the objectives have been traced guided to develop the outlined purposes.